Competition among Exchanges and Enforcement Policy - Caglio, Cecilia (IMF Working Papers; Working Paper, 2013)
In this paper, we explore how competition among stock exchanges, operated as self-regulatory organizations (SROs), affects the design of their members' surveillance. We develop a model where two for-profit SROs compete for trading volume, while brokers execute transactions on behalf of the investors and may misreport the true cash flow. The SROs can deter a fraud by announcing an investigation and imposing a monetary penalty.The success of the investigation depends upon both the amount of resources devoted to monitoring and the efficiency of monitoring technologies. We show that when contracts are incomplete and investors do not have perfect information about the monitoring efficiency, competition among exchanges induces a race to the bottom in enforcement policy and a reduction in total welfare, compared to the case of a monopolist SRO.